Exporting Judicial Review from the United States to China - Lee, Tahirih V. (Columbia Journal of Asian Law, 2005)
Is the American model of judicial review transplantable to China? As top American judges call for the export of American judicial review and the topic of judicial review is widely debated in legal circles in China, this question demands thorough exploration by today’s legal community. Deans at China’s leading law schools also lecture and write on the subject, even though it represents a departure from their scholarly specialties. In October of 1997, the PRC’s central government launched a program to reform the judiciary. Since then, and particularly since 2001, when the Supreme People’s Court took a bold step toward reviewing constitutional questions, Chinese judicial reform has been a hot topic in legal academia and, indeed, in the broader legal community. A focus on the American model is not foremost in these Chinese discussions, but it does appear among frequent references to judicial review outside China, some of which explicitly discuss the United States. However, such a focus is important in light of assertions by United States Supreme Court Justices Sandra Day O’Connor and Stephen Breyer that American-style judicial review can be and, indeed, should be transplanted anywhere. The implication of O’Connor’s and Breyer’s arguments is that the United States’ judicial review system should be the model for every other country’s court system because, in some essential way, it is the most robust version of judicial review.